Smile and dental aesthetics: a literature review - Funda Demir; Elif Aybala Oktay; Fulya Toksoy Topcu (Medicine Science, 2017)
The importance of dentofacial appeal in regard to the individual's psycho-social well-being is a proven fact. One of the most important factors that affect people's smiles is teeth. A dental restorations positive impact on the patient's smile, appearance, self-confidence and overall mental health can not be underestimated. In this review, the relation between smile and dental aesthetics is being addressed together with teeth, gum, face elements, aesthetics criteria and cases. [Med-Science 2017; 6(1.000): 172-7]